Pullout behaviour of suction embedded plate anchors in clay - Song, Zhenhe (Curtin University, 2008)
In recent years oil and gas mining has moved into increasingly deeper water in search of undeveloped fields. As water depths approach and exceed 3000 m conventional offshore foundation systems become inefficient and ineffective in stabilising platforms and floating production storage units. The trend of supporting structure design in deep water has been to install catenary and taut leg mooring systems. Consequently, many types of anchoring systems are being developed and used in order to withstand large mooring forces. The SEPLA (Suction Embedded Plate Anchor) is ideal for use in this situation. This project has employed advanced numerical techniques and centrifuge testing to study pullout behaviour of plate anchor foundations in different soil profiles and suction caisson installation effect with the aim of generating a robust framework for design. The behaviour of strip and circular plate anchors during vertical pullout in uniform and normally consolidated clays has been studied by means of small strain and large deformation finite element analyses. Both fully bonded (attached), and ‘vented’ (no suction on rear face), anchors have been considered. The current numerical results were compared with existing laboratory test data, finite element results and analytical solutions. This study showed that the ultimate pullout capacity factors (Nc) for deep embedment were 11.6 and 11.7 for smooth and rough strip anchors and 13.1 and 13.7 for smooth and rough circular anchors respectively. When the anchor base was vented, the soil stayed attached to the anchor base for deep embedment, and the pullout capacity was therefore the same as for the attached anchor. The separation depth ratio, Hs/B or Hs/D was found to increase linearly with the normalised strength ratio, su/γ'B or su/γ'D.Numerical simulation has been conducted to assess the bearing capacity for inclined pullout plate anchors. This bearing capacity analysis was performed by embedding the anchors in clay with different initial inclinations and different embedment ratios. Both the attached anchor base and vented base were evaluated. The results showed that the bearing capacities of the inclined plate anchors were associated with the inclination angles and base conditions. The separation depth of the plate anchors can be assessed by a simple equation from vertically pulled out plate anchors. Large deformation finite element analyses of plate anchor keying in clay has been performed. The effects of anchor thickness, anchor padeye eccentricity, anchor-soil interface roughness, soil shear strength, anchor submerged weight and soil disturbance have been studied with anchors in uniform or normally consolidated clays. The numerical results were compared with transparent soil test and existing centrifuge test data. The study showed that the RITSS method works well in simulating the anchor keying process. Anchor padeye eccentricity played an important role in anchor keying. A normalised anchor geometry ratio was used to estimate the loss in embedment during plate anchor’s keying. Both finite element analysis and centrifuge tests have been conducted to study the suction caisson installation effect. In finite element analysis, the soil disturbed zone varied from 3 times the caisson wall thickness to a full area inside a caisson.Centrifuge tests of suction embedded plate anchors were conducted in normally consolidated kaolin clay and transparent uniform soil. It can be concluded that the reduction in anchor capacity due to soil disturbance after suction caisson installation depends on re-consolidation time and soil sensitivity. The soil disturbance also reduced the loss of embedment during the anchor keying process.